2017
DOI: 10.3390/inorganics5020035
|View full text |Cite
|
Sign up to set email alerts
|

Product Selectivity in Homogeneous Artificial Photosynthesis Using [(bpy)Rh(Cp*)X]n+-Based Catalysts

Abstract: Due to the limited amount of fossil energy carriers, the storage of solar energy in chemical bonds using artificial photosynthesis has been under intensive investigation within the last decades. As the understanding of the underlying working principle of these complex systems continuously grows, more focus will be placed on a catalyst design for highly selective product formation. Recent reports have shown that multifunctional photocatalysts can operate with high chemoselectivity, forming different catalysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…[6] Thep reorganized structure of the chromophore and the catalyst prevents the formation of bioinactive NAD(P) dimers. [6,7] Additionally,c atalytic hydrogen evolution was observed for more than six times longer (650 hours) than for structurally similar tpphz-bridged photocatalysts. [2c, 8] However,t he use of Ru(tpphz)RhCp* as aphotocatalyst for hydrogen production shows ac atalytic activity much lower than for NAD + reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Thep reorganized structure of the chromophore and the catalyst prevents the formation of bioinactive NAD(P) dimers. [6,7] Additionally,c atalytic hydrogen evolution was observed for more than six times longer (650 hours) than for structurally similar tpphz-bridged photocatalysts. [2c, 8] However,t he use of Ru(tpphz)RhCp* as aphotocatalyst for hydrogen production shows ac atalytic activity much lower than for NAD + reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of sacrificial electron donors, it photocatalytically reduces nicotine amides, which are biologically usable NAD‐like (nicotinamide adenine dinucleotide) cofactors (Figure A) . The preorganized structure of the chromophore and the catalyst prevents the formation of bioinactive NAD(P) dimers . Additionally, catalytic hydrogen evolution was observed for more than six times longer (650 hours) than for structurally similar tpphz‐bridged photocatalysts .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the [Rh­(bpy)­(Cp*)­X] + catalyst is of particular interest for several reasons. It has been studied extensively for the reduction of a wide range of substrates (protons, ketones, NAD + , and flavins) either by a hydride donor (such as formate) or via electrochemical or photochemical reduction in the presence of protons. , Initially, Kölle and Grätzel have shown that this rhodium-based system could catalyze photochemical hydrogen generation by using weakly reducing electrons of a TiO 2 colloid . Subsequently, Deronzier et al and Gray et al have used [Rh­(bpy)­(Cp*)­X] + -derived catalysts in a homogeneous solution or immobilized on an electrode to study the electrochemical reduction of protons to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic process of this reduction works as follows: [ 50 ] sodium formate activates the catalytic Rh‐site and liberates carbon dioxide by β ‐hydride elimination to form the rhodium hydride complex. The hydride can then reduce the coordinated BNA + to the respective BNAH (see Figure and catalytic cycle sketched in Scheme S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%